2016
DOI: 10.1038/srep36223
|View full text |Cite
|
Sign up to set email alerts
|

SNP discovery and genotyping using Genotyping-by-Sequencing in Pekin ducks

Abstract: Genomic selection and genome-wide association studies need thousands to millions of SNPs. However, many non-model species do not have reference chips for detecting variation. Our goal was to develop and validate an inexpensive but effective method for detecting SNP variation. Genotyping by sequencing (GBS) can be a highly efficient strategy for genome-wide SNP detection, as an alternative to microarray chips. Here, we developed a GBS protocol for ducks and tested it to genotype 49 Pekin ducks. A total of 169,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Our results emphasize that detecting selective sweeps does not require phased haplotype data, as distortions in the frequency spectrum of MLGs capture the reduction in diversity under a sweep similarly well to phased haplotypes. Accordingly, the advent of rapid and cost-effective genotyping-bysequencing technologies (Elshire et al 2011) across diverse taxa including bovine, marine-dwelling, and avian populations means that the adaptive histories of myriad organisms may now be inferred from genome-wide data (Daetwyler et al 2014;Drury et al 2016;Zhu et al 2016). Furthermore, we have shown that the inferences emerging from MLGbased scans align with those of phased haplotype-based scans, with empirical analyses of human populations yielding concordant top outlying candidates for selection, both documented and novel.…”
Section: Discussionmentioning
confidence: 63%
“…Our results emphasize that detecting selective sweeps does not require phased haplotype data, as distortions in the frequency spectrum of MLGs capture the reduction in diversity under a sweep similarly well to phased haplotypes. Accordingly, the advent of rapid and cost-effective genotyping-bysequencing technologies (Elshire et al 2011) across diverse taxa including bovine, marine-dwelling, and avian populations means that the adaptive histories of myriad organisms may now be inferred from genome-wide data (Daetwyler et al 2014;Drury et al 2016;Zhu et al 2016). Furthermore, we have shown that the inferences emerging from MLGbased scans align with those of phased haplotype-based scans, with empirical analyses of human populations yielding concordant top outlying candidates for selection, both documented and novel.…”
Section: Discussionmentioning
confidence: 63%
“…Our results emphasize that detecting selective sweeps does not require phased haplotype data, as distortions in the frequency spectrum of MLGs capture the reduction in diversity under a sweep similarly well to phased haplotypes. Accordingly, the advent of rapid and cost-effective genotyping-by-sequencing technologies [Elshire et al, 2011] across diverse taxa including bovine, marine-dwelling, and avian populations means that the adaptive histories of myriad organisms may now be inferred from genome-wide data [Daetwyler et al, 2014, Drury et al, 2011, Zhu et al, 2016]. Furthermore, we have shown that the inferences emerging from MLG-based scans align with those of phased haplotype-based scans, with empirical analyses of human populations yielding concordant top outlying candidates for selection, both documented and novel.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh blood was collected from the ducks before slaughtering and genomic DNA was extracted from the blood using a phenol–chloroform-based method. Genotyping was performed using GBS, as described previously [15]. A total of 544 million clean reads (63.25 GB) were generated, of which 96.12% (523 million reads) were mapped to the duck genome, with an average mapping rate of 96.25%.…”
Section: Methodsmentioning
confidence: 99%
“…The data were deposited in the NCBI sequence read archive (SRP068685). GBS procedures are available on Zhu Feng’s article [15]. Restriction enzyme ( MSe1 ) for the PCR-RFLP assay was selected using information from REBASE [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation